A Discursive Void in a Cross-Language Study on Russia: Strategies for Negotiating Shared Meaning. (June 2019) - Outila, Virpi; Piekkari, Rebecca; Mihailova, Irina
ABSTRACT: Discursive voids in emerging markets present opportunities and challenges to debate meanings and taken-for granted assumptions. This article uncovers various strategies used by the researcher and the research participants to address the discursive void and to negotiate shared meaning about employee empowerment in Russia. In the absence of a concept for empowerment in the languages of the study, the researcher and the research participants engaged in joint sensemaking to bridge discursive voids. We contribute to the discussion of qualitative cross-language research in emerging markets by identifying the strategies used not only by the researcher, whose view has dominated previous research, but also those of the research participants. The researcher in our study addressed the discursive void by taking on the dual role of researcher-translator, engaging in contextual approach to translation, consulting external interpreters, and using iteration and flexibility in the course of the research process. Our research participants resorted to proverbs to address the discursive void, make sense of empowerment, and render it locally meaningful. Proverbs are a valuable methodological tool for sensemaking and theorising about context-specific phenomena in IB research. 摘要: 存在于新兴市场中的话语空白为词语的含义和想当然的假设之间的讨论提供了机遇和挑战。本文揭示了研究人员和研究参与者在解决话语空白以及协商有关俄罗斯员工授权的共享含义过程中所使用的各种策略。在研究语言中缺少关于授权这一概念的情况下，研究者和研究参与者进行了联合意义构建来弥补话语空白。我们不仅发现了在过去研究中占主导地位的研究者所使用的策略，而且还发现了研究参与者们所使用的策略，从而为新兴市场的定性跨语言研究做出了贡献。本研究中的研究者通过承担研究者-翻译者的双重身份，从语境角度入手从事翻译、咨询外部的翻译人员，并在研究过程中使用重复和灵活的方式来填补话语空白。研究参与者们则依靠谚语来填补话语空白，理解授权的意义并赋予其本土化的含义。谚语作为在国际商务研究中关于特定情境下现象的意义构建及其理论化方面具有价值的方法论工具。 АННОТАЦИЯ: В странах с развивающейся экономикой, дискурсивные пробелы одновременно открывают новые возможности и ставят трудные задачи для обсуждения смыслов и общепринятых предположений. В этой статье рассматриваются различные стратегии, которые исследователи и участники исследований используют для устранения дискурсивного пробела и формирования общего понимания о расширении прав и возможностей сотрудников в России. В отсутствие концепции расширения прав и возможностей на языках исследования, исследователь и участники исследования занимались совместным осмыслением для преодоления дискурсивных пробелов. Мы вносим свой вклад в область качественных межъязыковых исследований в странах с развивающейся экономикой, определяя стратегии, которые используют не только исследователь, чье мнение доминировало в предыдущих работах, но и участники исследования. Обратившись к дискурсивному пробелу, исследователь в нашей работе брал на себя двойную роль исследователя-переводчика и применял контекстный подход к переводу, с помощью других переводчиков, а также итерации и гибкости в процессе исследования. Наши участники исследования прибегали к пословицам, чтобы устранить дискурсивный пробел, осмыслить концепцию расширения прав и возможностей, а также придать ей контекстуальное значение. Пословицы являются ценным методологическим инструментом для осмысления и теоретизирования специфических контекстуальных явлений в исследованиях по международному бизнесу. RESUMEN: Los vació discursivos en mercados emergentes presentan oportunidades y retos para de debatir significados y supuestos dados por sentados. Este artículo deja descubierto varias estrategias usadas por la investigadora y los participantes de la investigación para abordar el vacío discursivo y negociación del significado compartido sobre el empoderamiento de los empleados en Rusia. En la ausencia de un concepto para empoderamiento en los idiomas del estudio, la investigadora y los participantes de la investigación participaron conjuntamente en dotar de sentido para superar los vacíos discursivos. Contribuimos a la discusión de la investigación cualitativa entre distintos idiomas en mercados emergentes al identificar las estrategias usadas no solo por la investigadora, cuya visión ha dominado la investigación anterior, sino también de los participantes de la investigación. La investigadora de nuestro estudio aborda el vacío discursivo asumiendo el doble papel de investigador-traductor, participando en un abordaje contextual para la traducción, consultando interpretes externos, y usando iteración y flexibilidad en el curso del proceso de investigación. Nuestros participantes de investigación recurrieron a proverbios para abordar los vacíos discursivos, dar sentido de empoderamiento y hacer que sea localmente relevante. Los proverbios son una herramienta metodológica valiosa para dar sentido y teorizar sobre los fenómenos específicos en la investigación de negocios internacionales.